Signal analysis of a polarimetric fiber optic sensor for dynamic strain monitoring - Bieda, Marcin S; Domański, Andrzej W.; Kuchta, Dawid; Lesiak, Piotr; Woliński, Tomasz R. (Photonics Letters of Poland, 2014)
Polarimetric fiber optic sensors have many advantages over other fiber optic sensors and strain gauges. As opposed to Fiber Bragg Grating sensors, polarimetric fiber sensors can be constructed with very simple, portable and robust experimental setup. In the paper we propose two methods of the polarimetric sensor output signal analyzing. First method is based on depolarization phenomena, and calculates degree of polarization (DOP), second one uses Fast Fourier Transform to analyze dynamic sensor response. Usefulness of both methods has been shown and experimentally proven. Full Text: PDF References K. Schroeder, W. Ecke, J. Apitz, E. Lembke, G. Lenschow, "A fibre Bragg grating sensor system monitors operational load in a wind turbine rotor blade," Meas. Sci. Technol. 17, 1167–1172 (2006). CrossRef G. Hegde, A. Asundi, "Performance analysis of all-fiber polarimetric strain sensor for composites structural health monitoring," NDT&E International 39, 320–327 (2006). CrossRef G. Wehrle, P. Nohama, H. J. Kalinowski, P. I. Torres, L. C. G.Valente, "A fibre optic Bragg grating strain sensor for monitoring ventilatory movements" Meas. Sci. Technol. 12, 805–809 (2001). CrossRef W. J. Bock, A. W. Domanski, T. R. Wolinski, "Influence of High Hydrostatic Pressure on Beat Length in Highly Birefringent Single-Mode Bow-Tie Fibers," Appl. Optics 29, 3484-3488 (1990). CrossRef A. W. Domański, M. Bieda, P. Lesiak, P. Makowski, M. Szeląg, T. Poczęsny, K. Prokopczuk, P. Sobotka, M. Chychłowski, M. Sierakowski, T. R. Woliński, "Polarimetric optical fiber sensors for dynamic strain measurement in composite materials," Acta Physica Polonica A. 124, 399-401 (2013). CrossRef P. Lesiak, G. Rajan, Y. Semenova, G. Farrell, A. Boczkowska, A. W. Domański, T. R. Woliński, "A hybrid highly birefringent fiber optic sensing system for simultaneous strain and temperature measurement," PLP 3, 140-142 (2010). CrossRef R. A. Chipman, "Depolarization in the Mueller Calculus," Proc. SPIE 5158, 184–192 (2003). CrossRef N. Furstenau, M. Schmidt, W. J. Bock, W. Urbanczyk, "Dynamic pressure sensing with a fiber-optic polarimetric pressure transducer with two-wavelength passive quadrature readout," App. Opt. 37, 663-671 (1998). CrossRef